Construction and Development of Perceived Marital Self Efficacy Scale - Busari, Afusat Olanike (Advances in Social Sciences Research Journal, 2019)
The study conceptualized on measures assessing efficacy in performing specific relationship behaviours as important and useful in understanding functioning within relationships, marriage including habitual patterns of behaviour. The purpose of the study, therefore, attempt to develop local instrument create for understanding of perceived marital self - efficacy as many of related instruments available are foreign ones. The marital self-efficacy scale was administered to 250 volunteers’ male and female married individuals of secondary school teachers. Personal identity and optimism instruments were also used to examine the predictive validity of perceived marital self-efficacy. Exploratory factor analysis determined that a three-factor solution was best fitting, explaining 45.77 percent of the variance, which was reproduced reliably in the subsamples. Through a series of factor model testing by confirmatory factor analysis, findings indicated that the two-factor structure was reliable, internally valid as demonstrated while no items were assigned to the third factor since the items did not meet criterion assigned. Subsequent, Pearson’s product moment correlation analysis also showed that there were positive significant relationship between factors in predicted perceived marital self-efficacy.